After Coal: Affective-Temporal Processes of Belonging and Alienation in the Deindustrializing Nottinghamshire Coalfield, UK - Emery, Jay (Frontiers in Sociology, 2020)
This article advances conceptualizations of belonging and alienation among deindustrializing people toward pluralistic temporal and affective processes. The focus is on belonging and alienation among a deindustrialized generation in the Nottinghamshire coalfield, UK, exploring how various affective-temporal processes mediate capacities, claims and senses of belonging and alienation. Extant studies suggest that multiple temporal processes constitute deindustrialized places: intergenerational transmissions, memory and place-histories. Recent work has explored the affective, emotional and embodied dynamics of these temporal processes. While these literatures are insightful in locating affective and temporal processes of belonging, studies do not have much to say on the relational dynamics of affective-temporal processes in everyday becoming lives and experiences of deindustrializing places. The significance of foregrounding relational affective-temporal processes of belonging and alienation is psychosocial and political. A coherent sense of belonging is fundamental for individual and social wellbeing, and the loss of belonging – alienation – informs the politics of former industrial places. Based on autoethnographic, interview and Observant Participation research with participants born between 1984 and 1994, I use ethnographic vignettes to delineate multiple relating affective-temporal processes of belonging and alienation of a generation that came after coal. The first vignette concerns the embodied and affective dynamics of intergenerational transmission. The second vignette investigates senses of alienation and the sticking of class backgrounds and historicities. The third vignette examines nostalgic and traumatic shared autobiographical memories contingent of living deindustrialization. The fourth vignette looks at intersections of place histories, silenced memory and local pride and shame, drawing out the significance of space and place to class-based experiences. Weaved through the stories are thematic threads of class, place, alienation, belonging and temporality. Bringing these threads together, the paper discusses the relationalities between issues covered, emphasizing the mutual contingencies between affective-temporal processes of belonging and alienation. I end by calling for shared affective-temporal processes of belonging and alienation to form the basis of a renewed solidarity, attenuation of alienation and a means to belong.